Implementation of Criminal Aspects by the Water Police in Law Enforcement in the Waters of Central Java (Research Study at the Directorate of Water and Air Police, Central Java Regional Police) - Pamungkas, Rendi; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2025)
Law enforcement efforts against perpetrators of maritime crimes are basically the function and duty of the Police as regulated in Law Number 2 of 2002 concerning the Indonesian National Police. All crimes, both general crimes and special crimes, where the crime scene or which falls within the jurisdiction of the Indonesian territorial waters and airspace will be the authority of the Directorate of the Marine and Air Police. The purpose of this research is toknow and analyze (1) criminal codification in the scope of waters in national legal construction, (2) the water police system in enforcing criminal law, (3) obstacles faced by the maritime police in enforcing maritime crime law. The approach method used in this study is sociological juridical. The specifications of this study are descriptive analytical. The data sources used are primary data and secondary data. Primary data is data obtained directly from the field or from the first source and has not been processed by other parties. Secondary data is data obtained from library research consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results of the research and discussion can be concluded: (1) Types of maritime crimes or certain criminal acts at sea can be grouped as follows: Armed Piracy or Piracy at Sea; Smuggling Crimes Through Sea Lanes (Smuggling); Criminal Acts in the Field of Shipping; Criminal Acts of Marine Pollution; Criminal Acts of Cultural Heritage Objects Under the Sea Surface; Criminal Acts Against the Management of Coastal Areas and Small Islands; Criminal Acts of Conservation of Biological Resources and their Ecosystems; Criminal Acts in the Exclusive Economic Zone of Indonesia; Criminal Immigration in Waters; and Criminal Acts of Fisheries. (2) The main duties of the Central Java Regional Police Polairud include a number of very important activities to maintain security, safety, and order in water and air areas. Several laws and technical regulations as legal legitimacy in providing reinforcement to the Water and Air Police in carrying out their authority as law enforcement institutions in water areas as investigators. (3) With such a wide territorial area, technically the Polairud problem in enforcing criminal law in Indonesian waters lies in the specifications of ships for water areas which are generally seas with large waves, accompanied by coral reefs, and ocean meeting routes.